2008
DOI: 10.1515/bot.2008.035
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, morphology and distribution of Pseudo-nitzschia calliantha, P. multistriata and P. multiseries (Bacillariophyta) from the northwestern Sea of Japan

Abstract: Toxicity, morphology and distribution patterns of three bloom-forming species of the diatom genus Pseudo-nitzschia (potential producers of the neurotoxin domoic acid and causative organisms of amnesic shellfish poisoning) from Peter the Great Bay in the northwestern Sea of Japan are presented. Pseudo-nitzschia calliantha, P. multistriata and P. multiseries bloomed in Peter the Great Bay in the fall, with abundances exceeding 106 cells l-1. This is the first report of toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 28 publications
4
8
0
Order By: Relevance
“…DA was found for the first time in stationary-phase P. multiseries cells isolated from Peter the Great Bay, at concentrations varying between 180 and 5390 ng DA ml À1 or 2-21 pg DA cell À1 (Orlova et al, 2008; Table 3). No DA was detected (<2 ng ml À1 ) in cultures of P. calliantha and P. multistriata from the same locality.…”
Section: Asiamentioning
confidence: 98%
See 1 more Smart Citation
“…DA was found for the first time in stationary-phase P. multiseries cells isolated from Peter the Great Bay, at concentrations varying between 180 and 5390 ng DA ml À1 or 2-21 pg DA cell À1 (Orlova et al, 2008; Table 3). No DA was detected (<2 ng ml À1 ) in cultures of P. calliantha and P. multistriata from the same locality.…”
Section: Asiamentioning
confidence: 98%
“…No DA was detected (<2 ng ml À1 ) in cultures of P. calliantha and P. multistriata from the same locality. A gamma proteobacterium (tentatively identified as Alteromonas macleodii) was isolated from P. multiseries strain PM-02 (Orlova et al, 2008), and was earlier shown to significantly enhance the DA concentration of an axenic culture of P. multiseries (S.S. Bates, I. Kaczmarska, C. Lé ger, J. Ehrman and D.H. Green, unpubl. data).…”
Section: Asiamentioning
confidence: 99%
“…Some strains of this species are toxic Bates & Trainer, 2006). However, Orlova et al (2008) did not detect any toxicity in a strain of P. calliantha from the Sea of Japan, and strains from the southern Gulf of St. Lawrence, Canada, were also below the limit of detection for DA (S. Bates, pers. comm.).…”
Section: Pseudo-nitzschia Callianthamentioning
confidence: 99%
“…multiseries has frequently been observed at densities >1000 cells ml À1 [52,55,69]. Reports of natural DA concentrations are, however, scarce [74] and range from 3 mg l À1 [23] to 136 mg l À1 [75].…”
Section: Discussionmentioning
confidence: 99%
“…Five replicates of 200 ml, containing 100,000 mussel embryos each, were exposed for 48 h. P. multiseries or P. lima were added at environmentally relevant bloom concentrations: 1400 cells ml À1 and 150 cells ml À1 , respectively [24,52]. Toxins were added to the highest non-lethal concentrations: 800 mg DA l À1 or 150 mg OA l À1 .…”
Section: Phenoloxidase Activitymentioning
confidence: 99%